Societal Perception on Chhori (Daughter) in Nepali Society - K.C., Raju (Nepalese Journal of Society and Culture, 2025)
This study explores the evolving socio-cultural and religious perceptions of Chhori-daughters-in Nepali society. Rooted in traditional Hindu rituals and symbolism, daughters are revered as embodiments of divine feminine energy, yet simultaneously constrained by patriarchal ideologies such as Parai Dhan (property of others). Through an emic lens and ethnographic insights, this study investigates the complex intersection of reverence and marginalization surrounding daughters. It reveals how festivals, rites of passage and shifting legal and feminist discourses are reshaping the societal role of daughters, while highlighting the enduring emotional bond symbolized by Maiti Ghar (natal home). The findings suggest both a persistent gendered structure and emerging spaces for equality and empowerment.